(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article provides a comprehensive analysis of flat needle knitting machines, detailing their structural components, operating principles, and various application areas. It examines the fundamental mechanisms that govern their functionality, including needle movement, yarn-feeding systems, and fabric formation techniques. Additionally, the study highlights modern advancements in knitting technology, such as automation, digital control systems, and material innovations that enhance production efficiency and fabric quality. The article also explores the significance of flat needle knitting machines in the textile industry, their role in producing diverse knitted fabrics, and their impact on sustainability through resource-efficient manufacturing processes.